Scrutinizing Islamic Higher Education Institutions in Indonesia - Nizar Alam Hamdani (Jurnal Pendidikan Islam, 2023)
In the era of globalization, Islamic higher education institutions (HEI) encounter obstacles concerning human resources, infrastructure, and technological proficiency. Based on the existing literature, empirical evidence and theoretical insights show that dynamic capability can enhance the performance of higher education in the era of digital transformation. The aim of this study is to examine Islamic HEI in Indonesia by comprehensively scrutinizing dynamic capacity, knowledge management, and information technology in improving the institutions’ performance. The research methodology employed is a quantitative approach utilizing descriptive and verification methods. There are 34 Islamic HEI served as the sample. Data analysis is conducted using the SEM-PLS technique. The findings of the study indicate that Islamic HEI in Indonesia possess preparedness in implementing knowledge management and demonstrated sufficient infrastructure to anticipate changes.